2022
DOI: 10.1515/med-2022-0487
|View full text |Cite
|
Sign up to set email alerts
|

Rack1 regulates pro-inflammatory cytokines by NF-κB in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is one of the chronic microvascular diseases of diabetes. Studies revealed that inflammation is involved in the development of DN. However, its mechanisms are not fully clear. Here, we screened DN-related mRNAs by RNA sequencing in the renal tissues of db/db DN mice and normal control mice. The Swiss-Model, ZDOCK 3.0.2 and PyMOL 2.3.2 were applied for bioinformatics analysis. In total, we obtained 6,820 mRNAs that were dysexpressed in DN. Among them, Receptor for Activated C Kinase 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…For example, RACK1 inhibits the recruitment of macrophages and regulates the differentiation of macrophages into the M2 macrophages, leading to an anti-inflammatory response, which promotes the development of tumours [ 18 ]. Wu et al found that RACK1 plays a regulatory role in the inflammation of diabetic nephropathy by interacting with the NF-κB subunits p50 and p65 [ 33 ]. Brugier et al found that RACK1 facilitates dengue virus infection by binding to the 40 S ribosomal subunit to recruit Vigilin and SERBP1, which is proposed to link viral RNA to the translation machinery to promote viral replication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, RACK1 inhibits the recruitment of macrophages and regulates the differentiation of macrophages into the M2 macrophages, leading to an anti-inflammatory response, which promotes the development of tumours [ 18 ]. Wu et al found that RACK1 plays a regulatory role in the inflammation of diabetic nephropathy by interacting with the NF-κB subunits p50 and p65 [ 33 ]. Brugier et al found that RACK1 facilitates dengue virus infection by binding to the 40 S ribosomal subunit to recruit Vigilin and SERBP1, which is proposed to link viral RNA to the translation machinery to promote viral replication [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been reported that RACK1 is a negative regulator of NF-κB signalling in TNF-α-treated 293T cells [ 36 ], classical swine fever virus-infected PK-15 cells [ 37 ] and Helicobacter pylori -infected gastric cancer cells [ 23 ]. However, RACK1 has been reported to be a positive regulator of NF-κB signalling in high glucose-treated mesangial cells [ 33 ] and PRRSV-infected Marc-145 cells [ 24 , 38 ]. These studies demonstrate that RACK1 is involved in the regulation of NF-κB activation, but it exerts positive or negative regulatory effects in response to different pathogens and different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been reported that RACK1 is identi ed as a negative regulator of NF-κB signaling in TNF-α-treated 293T cells [36] and classical swine fever virus-infected PK-15 cells [37] as well as Helicobacter pylori-infected gastric cancer cells [22]. However, RACK1 has been reported as a positive regulator of NF-κB signaling in high glucose-treated mesangial cells [32] and PRRSV infected Marc-145 cells [23,38]. These studies demonstrate that RACK1 is involved in the regulation of NF-κB activation but its positive or negative regulatory role is dependent on different pathogens and the response to different diseases.…”
Section: P Multocida Infection Promotes the Interaction Of Rack1 With...mentioning
confidence: 99%
“…For example, RACK1 inhibits the recruitment of macrophages and regulates macrophages to differentiate into M2 phenotype, leading to anti-in ammatory response, which promotes the development of tumors [18]. Wu et al found that RACK1 plays a regulatory role in the in ammation of diabetic nephropathy by interacting with NF-κB subunits p50 and p65 [32]. Alexis Brugier et al found that RACK1 facilitates Dengue virus infection by binding to the 40S ribosomal subunit to recruit Vigilin and SERBP1 which is proposed to link the viral RNA to the translation machinery to promote viral replication [33].…”
Section: P Multocida Infection Promotes the Interaction Of Rack1 With...mentioning
confidence: 99%
“…The widespread presence of a scaffolding protein receptor for activated protein kinase C1 (RACK1), which exhibits regulatory activity with protein kinase C (PKC) in both prokaryotes and eukaryotes, has garnered increasing attention and scrutiny [ 1 , 2 ]. As a highly conserved member of the tryptophan-aspartic acid domain (WD) repeat protein family, RACK1 participates in many biological processes, such as proliferation, cell migration, apoptosis, development, cellular adaptation processes, and immune responsiveness [ 1 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%